Dampak Pengasuhan Orang Tua Tunggal terhadap Kesejahteraan Anak - Alex R I Ompusunggu; Yani Achdiani; Gina Indah Permata Nastia (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2026)
Single-parent families are rising globally, prompting questions about their effects on children's well-being in diverse cultural settings. This study objectives to review recent evidence on the impact of single-parent upbringing on children's emotional, social, and physical welfare. A systematic literature review analyzed 35 peer-reviewed studies published between 2021 untill 2026 from databases including Google Scholar, PubMed, and Scopus, employing thematic analysis. Findings show single-parent children often exhibit emotional distress, lower academic performance, and behavioral challenges, yet display resilience in social skills and maturity with strong parental support physical health impacts link to socioeconomic factors. This synthesis calls for resilience-focused interventions to support affected families.